2018
DOI: 10.1111/1440-1681.12959
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 activates cytosolic phospholipase A2 via Ca2+‐dependent PKC/ERK1/2 signalling in controlling hypertensive contraction

Abstract: Activation of TRPV4 (transient receptor potential vanilloid 4) has been reported to result in endothelium-dependent contraction in the aortae of hypertensive mice. This contraction involved increased cPLA (cytosolic phospholipase A ) activity. The mechanism by which TRPV4 regulates cPLA activity to induce contraction in hypertension, however, is unknown. Through measurements of arterial tension and protein level, we showed that high-salt diet induced hypertension increases activity of PKC (protein kinase C) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Prostaglandin F2α (PGF2α) is the endothelium-derived contracting factor (EDCFs) induced by TRPV4 activation [32]. It was also shown that GSK1016790A or acetylcholine triggered the release of PGF2α (prostaglandin F2α) that was reduced by inhibition of PKC or ERK1/2 [33].…”
Section: Research Relation Tomentioning
confidence: 99%
“…Prostaglandin F2α (PGF2α) is the endothelium-derived contracting factor (EDCFs) induced by TRPV4 activation [32]. It was also shown that GSK1016790A or acetylcholine triggered the release of PGF2α (prostaglandin F2α) that was reduced by inhibition of PKC or ERK1/2 [33].…”
Section: Research Relation Tomentioning
confidence: 99%
“…Activation of TRPV4 by various stimuli leads to opening of the channel pore and influx of extracellular cations, particularly calcium, which initiate diverse downstream intracellular signaling cascades. [ 21 ] For example, TRPV4-mediated calcium influx been shown to affect signaling via ATP/pannexin, [ 22 , 23 ] nitric oxide, [ 24 , 25 ] phospholipase A2, [ 26 ] ERK1/2, [ 27 ] CaMKII, [ 28 , 29 ] and IP3, [ 30 , 31 ] among many others. [ 26 ] Notably, many of these signaling cascades converge on pathways that regulate cytoskeletal remodeling machinery.…”
Section: Introduction: Trpv4 Modulates Cell Physiology In Response To...mentioning
confidence: 99%
“…[ 21 ] For example, TRPV4-mediated calcium influx been shown to affect signaling via ATP/pannexin, [ 22 , 23 ] nitric oxide, [ 24 , 25 ] phospholipase A2, [ 26 ] ERK1/2, [ 27 ] CaMKII, [ 28 , 29 ] and IP3, [ 30 , 31 ] among many others. [ 26 ] Notably, many of these signaling cascades converge on pathways that regulate cytoskeletal remodeling machinery. For example, in trabecular meshwork cells of the eye, stretch-induced TRPV4 activation leads to phosphorylation of focal adhesion kinases and cytoskeletal stress fiber formation.…”
Section: Introduction: Trpv4 Modulates Cell Physiology In Response To...mentioning
confidence: 99%
“…Epithelial or endothelial cells express AQP1 and AQP5 (reviewed in [35]). PKC [36] can activate AQP1, whereas a transient receptor potential vanilloid 4 (TRPV4)-triggered [37] mechanism has been proposed for AQP5-mediated water flux reducing lung edema, potentially via PKC activation [38]. Ang II/AT1R mobilizes ENaC for Na + influx and its transit through the cell with the help of Na + /K + ATPase (detailed in Figure 4).…”
mentioning
confidence: 99%